2012
DOI: 10.1891/0047-2220.43.3.3
|View full text |Cite
|
Sign up to set email alerts
|

On Enhancing Competent Work with African American Clients: Challenging Persistent Racial Disparity Trends by Examining the Role of the Working Alliance

Abstract: Trends of racial disparities continue to persist across a variety of rehabilitation domains (e.g., acceptance rates, types of services offered, rehabilitation outcomes). African Americans consistently have poorer rehabilitation outcomes when compared to their White counterparts. Scholars have identified issues of racial bias in clinical judgment within cross-racial client-counselor relationships as a likely central factor contributing to this trend. The strength of the working alliance between counselor and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Research has shown that racial microaggressions are positively associated with alcohol use and problems (Blume, Lovato, Thyken, & Denny, 2012), and perceptions of racial bias have been reported in SUD treatment that may interfere with the working alliance (Davis & Ancis, 2012). Strangely, racism as a potential stressor related to substance use or as a potential threat to recovery from SUD seems to be rarely discussed by treatment professionals (Burris, 2012), and unwelcoming racial climates in treatment may be linked to poor treatment outcomes (Blume, 2016).…”
Section: Addressing Racial Trauma In Treatmentmentioning
confidence: 99%
“…Research has shown that racial microaggressions are positively associated with alcohol use and problems (Blume, Lovato, Thyken, & Denny, 2012), and perceptions of racial bias have been reported in SUD treatment that may interfere with the working alliance (Davis & Ancis, 2012). Strangely, racism as a potential stressor related to substance use or as a potential threat to recovery from SUD seems to be rarely discussed by treatment professionals (Burris, 2012), and unwelcoming racial climates in treatment may be linked to poor treatment outcomes (Blume, 2016).…”
Section: Addressing Racial Trauma In Treatmentmentioning
confidence: 99%
“…It could also support VR professionals to overcome cultural biases related to race and other consumer characteristics that contribute directly to inequities throughout the VR services program. For example, VR professionals could acquire specific skills for working with Black consumers and enhance the way they interact with Black consumers [ 62 ]. They could also identify inequities at all major junctures in the VR process and target those points for intervention to create change.…”
Section: Future Directionsmentioning
confidence: 99%
“…Self-awareness, an important part of cultural awareness, allows counselors to reflect on themselves and understand implicit biases during the delivery of cross-cultural counseling services. The theoretical framework for understanding the concept of cultural competence includes awareness of oneself and others, the knowledge of other cultures, and the ability to be non-judgmental in meeting certain cultural needs (Sudin, 2017); (Burris, 2016).…”
Section: Disscussionmentioning
confidence: 99%